Hydrogen bond driven self-supporting organogels from main-chain liquid crystalline polymers. (3rd February 2020) - Wang, Jing; Hao, Xingtian; Yan, Hongchao; Jiang, Qian; Peng, Haiyan; Xiong, Bijin; Liao, Yonggui; Xie, Xiaolin
Abstract: Main-chain liquid crystalline polymers (LCPs) have been widely investigated due to the excellent thermal stability and mechanical properties. In addition, hydrogen bond has been utilized to construct peptide supramolecular organogels by bottom-up approach but rarely to fabricate other supramolecular polymeric gels. In this work, some main-chain polymers with different proportion of pendent amide group have been designed and synthesized by melt polycondensation. The relationship between the liquid crystalline property and the proportion of amide group has been investigated by DSC and WAXD. Interestingly, among these polymers, the smectic main-chain LCP P100 with the highest molar ratio of amide group displays the best gelation ability with a minimum gelation concentration (MGC) of 2 wt% in THF. The hydrogen bond has been proved to be one of the most important driving forces for the gelation by NMR technique. The organogels exhibit good self-supporting ability with a storage modulus higher than 10 4  Pa when the gelator concentration is more than 4 wt%. At last, a hairpin model has been proposed to illustrate the microstructure for these organogels. These robust polymeric organogels that have been synthesized by bottom-up approach using hydrogen bond broaden the applications for main-chain LCPs ranging from actuators to electro-optical devices. Graphical abstract: Image 1 Highlights: A novel kind of organogels driven by hydrogen bond has been obtained from main-chain liquid crystalline polyester gelators. The liquid crystal properties and gel abilities can be regulated simply by the density of amide group in copolyesters. The organogel with low MGC displays excellent self-supporting ability.